Дієслова, що визначають глибину опрацювання предмета дослідження, та їх статистичні характеристики у науково-технічних текстах - Андрейчук, Н.; Волошиновська, І. (Лексикографічний бюлетень, 2006)
The list of key verbs denoting the stage of scientific research is suggested and their frequency analysis when used in scientific texts is viewed as means of determining of the depth of the subject of research cognition.